(untitled) (Tokyo, 1994)
These presentations were followed by a plenary discussion of operational issues, including the founding and maintaining of an international site network, applicability of Ramsar convention criteria to site selection and the development of a Shorebird action plan,...
Keywords: Water birds, Water birds,Chim biển; Conservation,Conservation,Sự bảo tồn; Asian,Australasian